Sosialisasi Pencatatan Keuangan Sederhana pada UMKM Kelurahan Sidodadi Kota Surabaya - Purnomo, Sahrial Hari; Majid, Nurkholis (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the national economy; however, many MSME actors still face limitations in business management, particularly in financial record-keeping. This condition is also found among MSME actors in Sidodadi Village, Simokerto District, Surabaya City, who have not yet implemented structured financial records. This socialization activity aims to improve the financial literacy and skills of MSME actors in preparing simple financial records, especially income statements. The method used in this activity consisted of socialization and staged mentoring over four weeks through observation, material delivery, implementation, and evaluation, involving three MSME actors. The results show an increase in participants’ understanding and awareness of the importance of financial record-keeping, where two participants were able to independently prepare income statements, while one participant still required further assistance. This activity has proven to have a positive impact on improving the business management of MSME actors. In addition, this activity can encourage a shift in mindset among MSME actors to separate business finances from personal finances as a basis for more structured and sustainable business decision-making.